The Role of the Educational Leadership Program Coordinator (PC) in University–K-12 School District Partnership Development. (December 2020) - Coleman, Lisa B.; Reames, Ellen
The researchers explored educational leadership program coordinator (PC) roles in developing university–K-12 school district partnerships. Little is known in regards to the PC's role in educational leadership preparation programs, and there is even less evidence of the PC's role in K-12 school district partnership development. This burden appears to have fallen in the educational leadership PC's wheelhouse. Using the Barnett et al.'s partnership model as the framework, the researchers examined the PC's role. Facilitating and hindering factors of sustainable partnerships were identified and investigated. Study outcomes suggested the PC is the chief collaborator in fostering K-12 school district partnerships.